Do antiepileptics have any potential to induce insulin resistance? A comparison between levetiracetam and valproic acid - Özer, Gökhan (The European Research Journal, 2019)
Objective: To explore whether levetiracetam and valproic acid are associated with insulin resistance and to determine their effects on glucose and insulin levels among different age groups. Methods: Demographic data were collected for epileptic patients from different age groups with a normal body mass index and no chronic endocrine disease who were on levetiracetam or valproic acid therapy. In addition to routine laboratory tests, fasting insulin level was checked and Homeostatic Model Assessment for insulin resistance calculated for all patients. Based on these measurements, the effects of levetiracetam and valproic acid on laboratory parameters were compared statistically. Results: A total of 61 patients (30 males, 31 females) diagnosed with epilepsy were included in the study. Thirty-four (55.7%) the patients were less than 15 years of age and the others were older. Twenty-three (37.7%) patients were on valproic acid therapy and 38 (62.3%) patients were receiving levetiracetam. Thirty-two (52.5%) the patients tested positive for insulin resistance and others were insulin resistance-negative. Nine (28.1%) patients on valproic acid treatment and 71.9% (n = 23) of patients on levetiracetam treatment were insulin resistance-positive. Conclusions: In the present study, contrary to the published literature, levetiracetam was found to be associated with further negative effects on insulin and blood glucose metabolism compared to valproic acid. We determined that levetiracetam had a distinct pharmacokinetic profile in pediatric patients as demonstrated by its effects on glucose and insulin metabolism.